Narratives of fear and safety - Kaukiainen, Kaisa; Kurikka, Kaisa; Mäkelä, Hanna; Nykänen, Elise; Nyqvist, Sanna; Raipola, Juha; Riippa, Anne; Samola, Hanna (Tampere University Press, 2020)
"The essays in this edited volume, written in English and French, tackle the intriguing problems of fear and safety by analysing their various meanings and manifestations in literature and other narrative media. The articles bring forth new, cross-cultural interpretations on fear and safety through examining what kinds of genre-specific means of world-making narratives use to express these two affectivities. The articles also show how important it is to study these themes in order to understand challenges in times of global threats, such as the climate crisis, and - to imagine a better future. The main themes of the book are approached from various theoretical perspectives as related to their literary and cultural representations. Recent trends in research, such as affect and risk theory, serve as the basis for the discussion. Many of the articles in the volume discuss apocalyptic and dystopian narratives that currently permeate the entire cultural landscape. Dystopian narratives do not only deal with future threats, such as totalitarianism, technocracy, or environmental disasters, but also suggest alternative ways of being and new hopes in the form of political resistance. The articles in the volume also draw from disciplines such as gender studies and trauma studies to examine the threats posed by collective fears and aggression on individuals' lives and propose ways of coping with fear. These themes are addressed also in articles analysing new adaptations of old myths that retell stories of the past."